Vieira entre outros: usos & abusos... - Carvalho, Carlos Roberto de (2006)
This text has as its mission and destiny to delineate, from the sermons, the letters and other writings from Antonio Vieira, a Jesuit priest and one of the most important men of the seventeenth century, the hybrid and ambiguous soul of the brazilian people. Mulatto, cafuzo (the offspring of black and Indian) and caboclo (the offspring of Caucasian and Indian) people mixed of white, black and Indian, whose basis lays on the amalgamation of the convergence and divergence of many cultures that have forged themselves on the land called Santa and Vera Cruz andthat nowadays is called Brazil. His main themes are: hybridism, ambivalence, post colonialism, colonization, evangelization, genocide, killing of the epistemology, America, Africa, Brazil, polyphony, dialogism, racism, dialectic, anthropology, ___ among many other things that his readers produce/ will produce, each one at his own time, according to their understanding, concerns and choices, at thee act of their reading, and that, therefore, impossible to condense them here, pray or say precise words. Not exactly!